Impacts of financial, caregiving, and emotional support on mental health: case of hypertensive patients in China - Tan, Jing; Kong, Deliang; Hu, Lin; Pu, Chuan (Frontiers in Public Health, 2025)
BackgroundHypertension and mental disorders, particularly depression, significantly impact Asia’s older adult. Alleviating depression in older adult hypertensive patients can significantly enhance their quality of life. This study evaluates the mental health status of hypertensive patients over 60 who do or do not provide intergenerational family support.MethodsUsing 2020 CHARLS data, we analyzed 4,851 hypertensive patients aged ≥60. Intergenerational family support was categorized into financial, daily caregiving, and emotional support, with mental health measured via the Chinese CESD-10. Multivariate linear regression and propensity score matching (PSM) assessed mental health changes from different support types. Heterogeneity analysis examined differences across age, gender, education, and urban–rural areas.ResultsCaregiving (β = −0.78, p < 0.01) and emotional support (β = −0.56, p < 0.05) significantly reduced depressive symptoms in older adult hypertensive patients, while financial support showed no significant impact. Sensitivity tests confirmed these results. Subgroup analyses revealed greater benefits for women (emotional support: β = −0.77), rural residents (emotional support: β = −0.59), and those aged ≥75 (caregiving support: β = −2.26).ConclusionNon-material intergenerational support, especially caregiving and emotional involvement, is crucial for alleviating depression in older adult hypertensive patients, whereas financial support has little effect. Policies should prioritize psychosocial interventions over financial aid, particularly for vulnerable groups like women, rural residents, and the older adult aged ≥75.